Enhancing Subjective Career Success Among Private University Academics: The Roles of Perceived Organizational Support, Proactive Personality, and Work Engagement - Nafiudin Nafiudin; Corry Yohana; Agus Wibowo (Journal of Applied Data Sciences, 2026)
This study aims to develop and empirically test a conceptual model explaining the determinants of subjective career success among academics in private universities in Indonesia. Drawing on Social Cognitive Career Theory (SCCT) and insights from the Job Demands–Resources (JD-R) theory, proactive personality is conceptualized as a personal resource representing person input and perceived organizational support as a contextual resource that influence career outcomes. In this framework, work engagement is proposed as a key motivational mechanism through which personal and organizational resources are translated into subjective career success. A quantitative research design was employed using a survey method administered to full-time academics at private higher education institutions across Indonesia. Data were collected from 278 respondents and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4. The results indicate that proactive personality and perceived organizational support exert positive and significant effects on subjective career success. Furthermore, work engagement partially mediates the relationships between proactive personality and subjective career success, as well as between perceived organizational support and subjective career success. These findings suggest that the availability of personal and organizational resources plays a critical role in shaping academics’ subjective career experiences. From a theoretical perspective, this study extends the application of SCCT by integrating motivational insights from JD-R theory, demonstrating how personal resources (proactive personality) and contextual supports (perceived organizational support) influence career outcomes through work engagement as a psychological mechanism. Practically, the findings offer insights for private university management in designing faculty development policies that foster work engagement and enhance subjective career success.